Peritoneal dialysis in acute kidney injury: twenty years of experience at a single center in a developing country - Ponce, Daniela [UNESP]; Bannwart, Julia [UNESP]; Silva, Maryanne Zilli Canedo [UNESP]; Zamoner, Welder [UNESP]; Dias, Dayana Bitencourt [UNESP]; Balbi, André Luís [UNESP] (Oxford University Press (OUP), 2025)
Background: This study aimed to explore the role of peritoneal dialysis (PD) in patients with acute kidney injury (AKI) in relation to metabolic and fluid control, outcome and risk factors for death. Methods: We performed a retrospective cohort study collecting data from a large reference Center in Brazil on patient characteristics, hospitalization, PD prescription and delivery, clinical outcomes and laboratory exams. We evaluated all patients who had been consecutively treated by PD between January 2004 and January 2024. Results: Four hundred eighty-seven patients were included. Median age was 64.02 ± 15 years, most of the patients were hospitalized in the intensive care unit (ICU) and needed vasoactive drugs and mechanical ventilation. Sepsis was the main cause of AKI followed by cardiorenal syndrome type 1. Uremia was the main indication for dialysis, followed by the need to meet metabolic and fluid demands. Blood urea nitrogen and creatinine levels stabilized after a median of four dialysis sessions. Fluid removal increased progressively and stabilized at around 2.320 ± 0.91 ml after four sessions. Mechanical complications occurred in 9.2% and peritonitis in 6.2% of patients. Regarding AKI outcome, 34.9% recovered renal function, 6.8% remained on dialysis for over 30 days, and 55.8% died. Technique failure occurred in 19.9% of the cases and the main cause was a mechanical complication. Age, hepatorenal syndrome, APACHE score and dropout from PD due to insufficient fluid control were identified as risk factors for death, while cardiorenal syndrome, need to meet metabolic and fluid demand as indication of dialysis, and negative fluid balance after 4 sessions of PD were identified as protective factors. Conclusion: PD may be an effective solution for AKI patients, allowing adequate metabolic and fluid control. Age, APACHE score, hepatorenal syndrome and dropout from PD were associated with death, while cardiorenal syndrome, need to meet metabolic and fluid demands as indication of dialysis, and negative fluid balance were positive prognostic factors.
Keywords: Acute kidney injury; Patient survival; Peritoneal dialysis